(untitled) (Global Journal of Management and Business Research, 2013)
The aim of this working paper is to identify the board structure types and variables that affect the corporate social responsibility strategy of the organizations. The main and core four types of board structures and determinants of corporate social responsibility strategy of the organizations have been identified in this working paper after studying and examining 35 research articles written by eminent scholars. These four types of board structure are: (1) having female directors on the board of directors greatly affects the corporate social responsibility strategy of the firms and such types of firms are appeared to be more philanthropic. (2) Outside or independent directors on board of directors also a major component in determining the organization’s corporate social responsibility strategy. (3) Tenure of directors also has positive effects on determination of corporate social responsibility strategy of the organizations and (4) Board size also plays an important role in planning and development of organization’s corporate social responsibility strategy.